Fungsi â€œFukugoudoushi â€“Te Iruâ€ Dalam Novel Jiorama Karya Natsuo Kirino - Apriani, Indah; Manurung, Rudi Hartono (Lingua Cultura, 2011)
Japanese is a language that comprises a unique grammar. Internal structure is its uniquenessÂ and can be studied like syntax. One study of Japanese language syntax is functions ofÂ â€œfukugoudoushiâ€ ã€Œã¦ ã„ã‚‹ã€. This theme was chosen to understand the whole functions ofÂ â€œfukugoudoushiâ€ ã€Œã¦ã„ã‚‹ã€. As the corpus of data, a Natsuo Kirinoâ€™s novel Jiorama is used. ThisÂ study implements descriptive analytical method and literature review. From the results obtained, it isÂ concluded that fukugoudoushi "ã¦ ã„ã‚‹" has six functions, where the main function shows sustainedÂ activity and activity result.